Green economy and ecotourism-based development model of Oling River Food, Banyuwangi - Auda Nuril Zazilah; I Putu Sudhyana Mecha; Nurhalimah (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2023)
This study aims to analyse the application of the concept of green economy and ecotourism to the tourist attraction of Oling River Food in Banyuwangi, East Java, Indonesia, as well as to form a model for developing the tourist attraction of Oling River Food. This study uses a case study approach. Data were collected by observation, documentation, and interviews. After the data is collected, an interactive analysis technique is carried out namely data reduction, data presentation, and conclusion. The results show that the tourist attraction of Oling River Food has implemented two indicators from five indicators of environmentally sound development and five indicators from ten indicators of the green economy concept. As for the concept of ecotourism, the tourist attraction of Oling River Food has implemented two indicators out of five indicators. The Oling River Food tourist attraction development model that is made contains the potential, problems, solutions, and outcomes. The tourist attraction of Oling River Food has potential that must be continuously developed. The development model built is expected to be the basis for the development of tourist attractions that still pay attention to environmental, economic, and social factors.